2000
DOI: 10.1111/1467-9566.00205
|View full text |Cite
|
Sign up to set email alerts
|

Daily and lifecourse contexts of smoking

Abstract: Smoking remains a key topic of research and debate within the field of health research in the social sciences. This article seeks to add the dimension of the smokers' and ex-smokers' perspectives to the debate in order to ground the importance of smoking in people's everyday lives. Data are drawn from 54 semi-structured interviews with smokers and ex-smokers involved in a study of their experiences and understandings of the place of smoking in their daily and long-term biographies. The rich accounts given by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Smoking is much more than the addictive effect of nicotine; the smoking habit is also the rituals that each smoker associates with their habit [10,11]. For example, smoking gestures (e.g.…”
mentioning
confidence: 99%
“…Smoking is much more than the addictive effect of nicotine; the smoking habit is also the rituals that each smoker associates with their habit [10,11]. For example, smoking gestures (e.g.…”
mentioning
confidence: 99%
“…A great body of quantitative research has assessed the impact upon well-being of each of these features separately, but the qualitative access to meaning constructions has allowed this study to envisage the links between concrete social constraints and psychological meanings, as well as the influence of the body, feelings, and sensations (Cornish, 2004;Cromby, 2007;Laurier, McKie, & Goodwin, 2000;Lyons & Chamberlain, 2006;Marks, 2002). Subjective well-being appears in this perspective as closely dependent on the possibility to engage in diversified activity through dialectical intertwinements that contribute to professional and personal growth (Wallon, 1942).…”
Section: Discussionmentioning
confidence: 99%
“…These anti-smoking measures are justified by epidemiological knowledge about the health risks of smoking (Heikkinen et al, 2010). The problem looks simple; smoking is bad for your health, therefore stop smoking (Laurier, McKie, & Goodwin, 2000). However, as many previous studies (Petersen & Lupton, 1996;Frohlich, Corin, & Potvin, 2001;Dennis, 2013) have indicated, such individualistic understandings of smoking tend to ignore social, cultural, economic, and political circumstances as if there were no sociocultural contexts, systematic influences, or social meanings given to the behaviour.…”
Section: Introductionmentioning
confidence: 99%